2008
DOI: 10.1210/jc.2008-0760
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Activation and Dephosphorylation of Glycogen Synthase in Skeletal Muscle of Women with Polycystic Ovary Syndrome Is Reversed by Pioglitazone Treatment

Abstract: Impaired insulin activation of GS including absent dephosphorylation at sites 2+2a contributes to insulin resistance in skeletal muscle in PCOS. The ability of pioglitazone to enhance insulin sensitivity, in part, involves improved insulin action on GS activity and dephosphorylation at NH2-terminal sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
3
35
1
Order By: Relevance
“…Similar to the inconsistent finding of impaired insulin action on AKT phosphorylation (6,7,(11)(12)(13), this probably reflects the large heterogeneity in both type 2 diabetic and obese non-diabetic individuals combined with the relatively small sample sizes often used in such studies. However, the impaired insulin activation of GS and the lack of dephosphorylation of GS at sites 2+2a appear to be consistent findings in type 2 diabetic patients [3,7], as well as in other insulin-resistant conditions such as PCOS [9] and HIV lipodystrophy [37]. Consistently, we have demonstrated that insulin-mediated dephosphorylation of GS at sites 2 + 2a correlates significantly with insulinstimulated NOGM in a large cohort of twins [38].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to the inconsistent finding of impaired insulin action on AKT phosphorylation (6,7,(11)(12)(13), this probably reflects the large heterogeneity in both type 2 diabetic and obese non-diabetic individuals combined with the relatively small sample sizes often used in such studies. However, the impaired insulin activation of GS and the lack of dephosphorylation of GS at sites 2+2a appear to be consistent findings in type 2 diabetic patients [3,7], as well as in other insulin-resistant conditions such as PCOS [9] and HIV lipodystrophy [37]. Consistently, we have demonstrated that insulin-mediated dephosphorylation of GS at sites 2 + 2a correlates significantly with insulinstimulated NOGM in a large cohort of twins [38].…”
Section: Discussionsupporting
confidence: 87%
“…Glycogen synthase activity Muscle GS activity in the presence of 8, 0.17 or 0.02 mmol/l G6P was measured in triplicate using a 96-well plate assay (Unifilter 350 Plates, Whatman, Cambridge, UK) [7,9]. GS activities are reported either as total GS activity (determined at 8 mmol/l G6P), the percentage of G6P-independent GS activity (%I-form) (100×activity in the presence of 0.02 mmol/l G6P divided by the activity at 8 mmol/l G6P [saturated]) or as the percentage of fractional velocity (%FV) (100×activity in the presence of 0.17 mmol/l G6P divided by the activity at 8 mmol/l G6P).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, together with differences in sex composition and a lower baseline V : O 2max , may explain these discordant findings. Mutational studies [18,19] as well as analysis on muscle biopsies from humans [15,21,22,29] have found phosphorylation of GS at sites 2+2a and 3a+3b to be the most important for GS activity. In accordance, we demonstrate an inverse correlation between both insulin-and exercise-induced measures of GS activity and GS phosphorylation at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…2). It has been shown that insulin stimulation leads to GS dephosphorylation at sites 2ϩ2a and that such response is impaired in patients with T2DM and in women with polycystic ovary syndrome (5,45). Considering that subjects after the glycogen depletion protocol on day 1 went home and had a low carbohydrate dinner, dephosphorylation of GS at sites 2ϩ2a in pre-depleted muscle could respond to insulin stimulation during the postprandial state.…”
Section: Discussionmentioning
confidence: 99%